2018
DOI: 10.1093/eurpub/ckx225
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to health care services for migrants living with HIV in Spain

Abstract: Health care barriers were present in one in five5 MLWH, were more common in men and were associated to legal entitlement to access care, perceived stigma and financial constraints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 28 publications
1
16
0
2
Order By: Relevance
“…Lack of proficiency in the host country's language among MLWH was the second most reported barrier impeding initial access to care and treatment at the individual level. 56 , 58 , 62 , 63 , 65 , 66 , 68 , 70 , 77 , 80 , 82 , 85 , 86 , 94 , 102 , 105 Language seemed to amplify navigation-related challenges in particular. 77 , 102 For example, physically navigating clinics and hospitals in North Carolina was made difficult due to lack of Spanish signage.…”
Section: Resultsmentioning
confidence: 99%
“…Lack of proficiency in the host country's language among MLWH was the second most reported barrier impeding initial access to care and treatment at the individual level. 56 , 58 , 62 , 63 , 65 , 66 , 68 , 70 , 77 , 80 , 82 , 85 , 86 , 94 , 102 , 105 Language seemed to amplify navigation-related challenges in particular. 77 , 102 For example, physically navigating clinics and hospitals in North Carolina was made difficult due to lack of Spanish signage.…”
Section: Resultsmentioning
confidence: 99%
“…These barriers are not specific to HIV-related healthcare services and have been described widely in other studies regarding access to healthcare among migrants [13]. Although almost all participants were registered at a GP and migrants living with HIV in the Netherlands experience less difficulties accessing healthcare than migrants in some other countries in Europe [9, 14], these structural barriers in the access to care for migrants need to be addressed. In the Netherlands, all residents (including asylum seekers and refugees) are entitled to a basic health insurance package which includes the bulk of essential healthcare (including care provided by a GP), medications and medical aids [15].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, results from two qualitative studies ( 33 , 34 ) carried out in Catalonia about the needs and perceptions of healthcare providers on the provision of healthcare to migrants, suggested that communication barriers and low levels of cultural competency among professionals were the largest contributors to poor outcomes. Similarly, in a separate study of health-access barriers facing migrants with HIV ( 35 ), researchers found communication barriers were the main obstacle facing migrants of non-Spanish speaking countries.…”
Section: Discussionmentioning
confidence: 96%
“…These barriers could lead to delays in diagnosing and treating different diseases that carry not only individual, but important public health consequences such as tuberculosis, HIV, hypertension, diabetes, hepatitis B and C, schistosomiasis, strongyloidiasis, and Chagas ( 36 ). For example, in the previously mentioned study of migrants with HIV ( 35 ), 14–25% of migrants who reported barriers to healthcare access had been diagnosed with late HIV. Furthermore, increasing migrant engagement with preventive health initiatives such as vaccination and/or LTBI screening campaigns may confer benefits on them and the community ( 5 , 37 – 39 ).…”
Section: Discussionmentioning
confidence: 99%